Urinary Interleukin 6: A Prognostic Bio Marker in Lupus Nephritis (Academia Journal of Medicine, 2019)
Background: Lupus nephritis is an frequent and potentially serious complication of SLE. It is an inflammatory disease of connective tissue  and immune system, where we find organs and cells undergo damage initially mediated by tissue-restricting auto antibodies and immune  complexes. Our aim was to evaluate the association of urinary interleukin 6 in lupus nephritis patients and validate its use as a prognostic  marker. For this we took the complete demographic profiling of the participant patients along with all biochemical parameter were checked.  For IL-6 analysis, we analyzed the whole immunological profile and correlated the level of urinary proteins, serum creatinine and urinary IL-6.  The mean values of urinary IL-6 at presentation and after 6 months of treatment were calculated. Any change after 6 months was noted and  correlation of Il-6 with disease activity scores was observed. Urinary IL-6 was found to be significantly high in patients of lupus nephritis than  controls. Urinary IL-6 was higher in patients of severe form of lupus nephritis such as Class IV than other classes of lupus nephritis. Urinary  IL-6 may be used as a prognostic marker of lupus nephritis. The patients who achieved complete remission had near normal levels of urinary  IL-6 and patients with partial remission had decreased level of urinary IL-6 than at presentation after 6 months of induction phase treatment.  But patients with no remission did not show any significant decrease in urinary IL-6 levels at 6 months. So, urinary Il-6 may be used to  monitor the response to therapy.
Keywords: Urinary IL-6; Lupus nephritis; Bio marker; Urinary protein